Claude Montefiore and Christianity - Bowler, Maurice Gerald (Brown Judaic Studies, 2020)
Claude Montefiore (1858-1938) was among the major founders of Anglo-Liberal Judaism and the World Union for Progressive Judaism, and was known for his radical ideas and deep sympathy for Christian ideas. This volume explores why and how Montefiore engaged Christianity, and the reaction to this engagement by many contemporary Jewish luminaries.